2016
DOI: 10.3389/fnagi.2016.00116
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes Following Perinatal Asphyxia: Role of Astrocytes and Their Interaction with Neurons

Abstract: Perinatal Asphyxia (PA) represents an important cause of severe neurological deficits including delayed mental and motor development, epilepsy, major cognitive deficits and blindness. The interaction between neurons, astrocytes and endothelial cells plays a central role coupling energy supply with changes in neuronal activity. Traditionally, experimental research focused on neurons, whereas astrocytes have been more related to the damage mechanisms of PA. Astrocytes carry out a number of functions that are cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 260 publications
(316 reference statements)
0
7
0
Order By: Relevance
“…Astrocytes are also involved in neural regeneration, synapse generation, and the formation and maintenance of the blood-brain barrier (Abbott et al, 2006;Perea et al, 2009;Lanciotti et al, 2013). Studies have found that there is a close relationship between astrocytes and neurons (Logica et al, 2016;Rose and Chatton, 2016). The migration, survival, and formation of synaptic connections in neonatal neurons require the guidance and support of astrocytes.…”
mentioning
confidence: 99%
“…Astrocytes are also involved in neural regeneration, synapse generation, and the formation and maintenance of the blood-brain barrier (Abbott et al, 2006;Perea et al, 2009;Lanciotti et al, 2013). Studies have found that there is a close relationship between astrocytes and neurons (Logica et al, 2016;Rose and Chatton, 2016). The migration, survival, and formation of synaptic connections in neonatal neurons require the guidance and support of astrocytes.…”
mentioning
confidence: 99%
“…For instance, astroglia take up glucose from the brain capillaries via their end-feet and deliver to neuronal axons (Baltan 2015). While glucose is the primary energy source which fuels the tricarboxylic acid (TCA) cycle, other nutrients, such as ketone bodies and lactate, are used for neuroenergetics when the glucose supply runs low or during high neuronal demand (Logica et al, 2016). In the brain, β-oxidation of free fatty acids (FFA) yields acetyl-CoA molecules for the TCA cycle to generate ATP (Guzmán, & Blázquez 2004).…”
mentioning
confidence: 99%
“…As well, our results demonstrate that SHR astrocytes submitted to CoCl 2 treatment present a decrease in Lactate in relation to untreated SHR cells, indicating that Lactate could be reappointed to other intracellular signalling pathways. It is known that under intense hypoxia a great amount of Lactate is extruded or deviated to glutamate synthesis 106108 . In this case, hypoxia can promote the activation of monocarboxylate transporter 4 (MCT4), which transports the Lactate out of the cell 106 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that under intense hypoxia a great amount of Lactate is extruded or deviated to glutamate synthesis 106108 . In this case, hypoxia can promote the activation of monocarboxylate transporter 4 (MCT4), which transports the Lactate out of the cell 106 . Furthermore, it can be suggested that higher levels of Lactate could provide more substrates for the conversion of glutamine to glutamate and could increase glutamate oxidation and its conversion into alpha-ketoglutarate; both processes are recognized as the essential functions to astrocytes 106108 .…”
Section: Discussionmentioning
confidence: 99%